The Use of Picture to Improve Reading Ability or Understanding Descriptive Text - Kondo, Yustina Cici; Hadiwijaya, Munawwir (Journey: Journal of English Language and Pedagogy, 2022)
This research investigates the use of picture media to improve students’ ability to read and understand descriptive texts. The study addresses three main questions: (a) How is picture media implemented to enhance reading comprehension of descriptive texts? (b) How does picture media improve students’ comprehension of descriptive texts? and (c) How does picture media improve students’ overall reading ability? The participants were 25 seventh-grade students of SMP Negeri 2 Kodi Utara, Sumba Barat Daya, who were taught using picture-based learning to support comprehension development. The study employed Classroom Action Research (CAR), conducted in two cycles, with each cycle consisting of planning, action, observation, and reflection. Data were analyzed using descriptive and statistical techniques. The results show a clear improvement in students’ reading comprehension through the use of picture media. This improvement is reflected in the increase from the pre-test mean score of 1.164 in Cycle I to the post-test mean score of 1.936 in Cycle II. These findings indicate that picture media effectively enhances students’ reading ability in descriptive text learning.